LAS RELACIONES HUMANAS Y SU INCIDENCIA EN LA CONVIVENCIA LABORAL DE LOS TRABAJADORES DEL HOSPITAL BÁSICO 7BI LOJA Y LA INTERVENCIÓN DEL TRABAJADOR SOCIAL - Barragàn Ochoa, Adriana del Carmen (2015)
This research focuses on how the "Poor human relations affect the labor coexistence of staff working in the Basic 7BI Loja Hospital" so that they remain human relations understood as the process of interaction of social subjects, are central to building a balanced and harmonious atmosphere in the society in which we live. The aim is to promote human society in all its manifestations, to strengthen the human and banish all that is opposed to the good understanding between men and women. To achieve this purpose was proposed as general objective: Strengthen Human Relations to help improve labor coexistence Staff; as well as specific objectives: Understand causes and effects of human relationships and their impact on Coexistence Labor Workers "Basic 7BI Loja Hospital," Justify theoretically and methodologically categories and variables of human relations, labor coexistence and Intervention Social Worker, Ask a proposal to improve human relations, personnel working in the "Basic 7BI Loja Hospital" and is performed by the same This research work was carried out under the methodology of the abstract to the concrete, through the intervention model reality with its phases and levels it reached the fourth phase, describe, analyze and interpret the data obtained in the level study is descriptive, because the events are listed, and collected information through the use of techniques and instruments such as the interview, direct observation and survey, the same as those applied to officials, medical personnel; and finally users in order to obtain accuracy and reliability of the research. Once collected the information is found that: poor human relations and coexistence influence job performance, likewise, communicating directly influences the low productivity and organizational development 7BI Loja Base 5 Hospital, and in the activities of workers. On the other hand the lack of companionship is another factor that diminishes the strength of interpersonal relationships among employees. Under this approach a proposal is presented to the hospital to be executed by it, from the perspective of Social Work